Evolution of acoustic communication in crickets: phylogeny of Eneopterinae reveals an adaptive radiation involving high-frequency calling (Orthoptera, Grylloidea, Eneopteridae) - Robillard,Tony (2004)
Evolution of dominant frequencies in songs of Eneopterinae crickets was studied with respect to phylogeny. Two characters are optimized on the tree: the first describes the frequency resulting from the vibration of the harp (Fda), and the second is due to the vibration of other tegminal areas (Fdb). Fda was found to be relatively stable through the subfamily. Its low ancestral state is replaced by a high Fda only once, resulting in high-frequency calling in [Cardiodactylus (Lebinthus-Agnotecous)]. A high Fdb component is added to the low ancestral Fda in Eneoptera guyanensis, resulting in frequency modulation. The onset of high Fd in this first subclade is accompanied by a high cladogenesis rate, which supports a hypothesis of adaptive radiation for high frequencies. The effectiveness of high-frequency calling is discussed in relation to the species behavior ecology.